Sarcopenic obesity in liver disease: Handling both sides of the penny. Issue 1 (31st May 2022) - Hui, Yangyang; Cui, Binxin; Wang, Xiaoyu; Sun, Mingyu; Li, Yifan; Yang, Wanting; Guo, Gaoyue; Mao, Lihong; Yu, Zihan; Fan, Xiaofei; Sun, Chao
Abstract: Skeletal muscle and fat tissue show distinct pathophysiological roles and pivotal functions. The culmination of muscle wasting and fat accumulation represents an opposite terminal of each state. Specifically, this situation has been designated as sarcopenic obesity. However, sarcopenic obesity still lacks a unanimous definition, diagnostic criteria, and generalized modalities for assessment in the context of versatile liver diseases. Moreover, the underpinning mechanisms by which a combination of abnormal skeletal muscle and fat tissue leads to the progression of liver disease and impairs health‐related consequences are still elusive. Additionally, the interplay between skeletal muscle and fat, and the driving factors that shift different body compositions are not well understood. Therefore, in this review, we discuss skeletal muscle and fat components, with the purpose of conceptualization, as well as interpret their roles in liver diseases. We focus on the definitions, diagnostic criteria, and currently available measurements for sarcopenic obesity in the literature. We comprehensively discuss recent data and evidence regarding the potential role of sarcopenic obesity in the development and progression of numerous liver diseases and associated conditions, including nonalcoholic fatty liver disease, chronic viral hepatitis, cirrhosis, and liver transplantation. Furthermore, explicit information related to the pathogenesis of sarcopenic obesity from basic research is also provided in this narrative review. Finally, we discuss, from the clinical perspective of view, how to manage sarcopenic obesity using nutritional, physical, and pharmacological methods. Abstract : The multifactorial and complicated pathogenesis of sarcopenic obesity in the context of liver diseases. Highlights: Sarcopenic obesity may contribute to the development and progression of various liver diseases. The pathogenesis of sarcopenic obesity in the context of liver diseases is multifactorial and complicated. Potential avenues for therapeutic intervention by modifying sarcopenic obesity are urgently required.